Applications of Advanced Technology in Transportation 2006
DOI: 10.1061/40799(213)50
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Activity-Travel Diary Data Collection Using a GPS-Enabled Personal Digital Assistant

Abstract: Activity-based transportation models have set the standard for modelling travel demand for the last decade. It seems common practice nowadays to collect the data to estimate these activity-based transportation models by means of activitytravel diaries. This paper presents a general functional framework of an advanced activity-travel diary data collection application to be deployed on a GPS-enabled personal digital assistant (PDA). The different modules, which are the building blocks of the application, will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Axhausen 1995;Stecher et al 1996;Stopher 1992Stopher , 1996Stopher , 2007Hawkins and Stopher 2004). An option of dynamic activity-travel diary data collection using global positioning systems (GPS) with a GPS-enabled personal digital assistant has been explored by Kochan (2004). Martin (2006) suggested that the application of information and communication technology (ICT)-enabled activity and travel surveys can increase response rates.…”
Section: Introductionmentioning
confidence: 99%
“…Axhausen 1995;Stecher et al 1996;Stopher 1992Stopher , 1996Stopher , 2007Hawkins and Stopher 2004). An option of dynamic activity-travel diary data collection using global positioning systems (GPS) with a GPS-enabled personal digital assistant has been explored by Kochan (2004). Martin (2006) suggested that the application of information and communication technology (ICT)-enabled activity and travel surveys can increase response rates.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature shows that wearable GPS travel studies have been conducted world-wide, including in the United States (Giaimo et al, 2009), United Kingdom (Steer Davies Gleave andGeostats, 2003), Japan (Ohmori et al, 2005), Belgium (Kochan et al, 2006), Netherlands (Bohte and Maat, 2008), and South Africa (Krygsman and Nel, 2009). Steer Davies Gleave and Geostats (2003) examined data from a wearable GPS subsample of London Area Transport Survey respondents for a threeday period.…”
Section: Gps In Household Travel Surveysmentioning
confidence: 99%
“…On the other hand, a software application called Parrots that runs on personal digital assistants was used. More information on data collection using Parrots is available in Kochan et al (14) and Bellemans et al (25).…”
Section: Feathers Travel Survey Conducted In Flandersmentioning
confidence: 99%